EVALUATION OF FENDER, BOLDER AND TRESTLE NEEDS AT BITUNG FERRY PORT, NORTH SULAWESI PROVINCE. - Widjatmoko, Eko Nugroho; Pusriansyah, Ferdinand; Seno, William; Sari, Desti Yuvita; Anwar, Andhika Faisal (IWTJ : International Water Transport Journal, 2024)
Bitung ferry port is a port that connects Lembeh Island, Talaud Island, Ternate Island and North Halmahera Island. The dock facilities at Bitung Ferry Port are in poor condition and have not met the standards in accordance with the Decree of the Minister of Transportation Number KM 52 of 2004. To realize the implementation and appropriate operations, an evaluation of the dock facilities at the ferry port is needed. This research uses descriptive quantitative research. The author analyzes fenders and fender spacing analyzes the number of bolder and bolder spacing and analyzes efforts to maintain fenders, bolder and trestle. The results of this study, the type of fender that is in accordance with the impact strength of the ship is type V 600H with the number of fenders 7 and each fender is given a distance of 10.65 meters. In the bolder, the number of bolder that is in accordance with the characteristics of the operating ship is 4 bolder with a distance between bolder is 23.67 meters. The condition of the existing trestle at the Bitung Ferry Port, it is known that the condition of the asphalt section has cracked. The conclusion of this research is that the condition of the fenders, bolder and trestle at the Bitung Ferry Port is not in accordance with the needs. PT ASDP Bitung Branch does not have a routine schedule and appropriate Standard Operating Procedure stages in carrying out regular maintenance. There needs to be a routine schedule for fender, bolder and trestle maintenance.